Effects of Family History and APOE ε4 Status on Cognitive Decline in the Absence of AD: The Cache County Study - Hayden, Kathleen M. (2009)
CONTEXT: Studies have shown that the APOE ε4 genotype is associated with cognitive decline and increased risk of Alzheimer’s dementia (AD). Other genes are probably associated with both outcomes. Family history of AD (FhxAD) may represent genetic factors or shared environmental factors that increase the risk of cognitive decline. OBJECTIVE: To evaluate the influences of FhxAD and APOE ε4 on cognitive decline. DESIGN, SETTING, AND PARTICIPANTS: Residents of Cache County, Utah, aged 65+ were invited to participate. At baseline 2,957 participants provided DNA for genotyping at APOE and a detailed family history of AD. They also completed the Modified Mini-Mental State Examination (3MS). Cognitive status was re-examined after three and seven years. We used mixed models to examine the association between FhxAD, APOE ε4, and cognitive trajectories. MAIN OUTCOME MEASURE: 3MS score trajectories over time. RESULTS: Compared with participants who had neither APOE ε4 nor FhxAD, those with APOE ε4 scored lower at baseline (−0.70 points on 3MS, 95% confidence interval (CI) −1.15 to −0.24). Participants with both FhxAD and APOE ε4 differed less, if at all, in baseline score (−0.46, 95% CI −1.09 to 0.16) but declined faster over 7 years (− 9.75, CI −10.82 -- 8.67) vs.(−2.91, CI −3.37 to −2.44). After exclusion of participants who developed prodromal AD or incident dementia, the group with FhxAD and APOE ε4 declined much less over 7 years (−1.54, CI −2.59 to −0.50). CONCLUSIONS: These results suggest that much of the association between FhxAD, APOE ε4, and cognitive decline is attributed to undetected incipient (latent) disease. Absent this association, the two factors do not appear individually to be associated with cognitive decline although they may be additive.